History of the Changes in the Roof Structure of a Historical Wooden Church - Hulimka, Jacek; Tunkel, Magda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the many years of exploiting building structures, many changes and reconstructions were carried out. Sacral structures were no exception. The article shows an example of a historical wooden church, in which at some point in time the roof was reconstructed. As a result of the above, the system of ridgepoles typical for wooden Silesian churches was destroyed. In 2012 the structure was renovated, bringing back the original roof arrangement. However, this required a change in the geometry of the secondary elements of the structure which did not fit with its original body. After, the works were completed the building regained its original system of ridgepoles, while the secondary elements were reconstructed, thus eliminating the existing problems with water drainage.
Keywords: wooden church; wooden roof; reconstruction; renovation; roof drainage